A Review on Iron Oxide‐Based Nanoarchitectures for Biomedical, Energy Storage, and Environmental Applications. Issue 5 (25th March 2019) - Tanaka, Shunsuke; Kaneti, Yusuf Valentino; Septiani, Ni Luh Wulan; Dou, Shi Xue; Bando, Yoshio; Hossain, Md. Shahriar A.; Kim, Jeonghun; Yamauchi, Yusuke
Abstract: Iron oxide nanoarchitectures with distinct morphologies from 1D to 3D have been developed using various wet chemical methods. They have been employed for a wide range of applications, including energy storage, biomedical, and environmental applications. The functional properties of iron oxide nanoarchitectures depend on the size, shape, composition, magnetic properties, and surface modification. To overcome the limitations of pure iron oxide nanostructures, hybridizations with various inorganic materials (e.g., silica, metals, metal oxides) and carbon‐based materials have been proposed. Herein, the recent advances in the preparation of various iron oxide nanoarchitectures are reviewed along with their functional applications in energy storage, biomedical, and environmental fields. Finally, the effects of various parameters on the functional performance of iron oxide nanostructures for these applications are summarized and the trends and future outlook on the development of iron oxide nanoarchitectures for these applications are also given. Abstract : This review summarizes the recent progress in the fabrication of iron oxide nanoarchitectures from 0D to 3D structures and their hybridization with various carbon‐based materials and inorganic materials for energy storage, biomedical, and environmental applications.